Hand Focused Upper Extremity Rehabilitation in the Subacute Phase Post-stroke Using Interactive Virtual Environments - Merians, Alma S.; Fluet, Gerard G.; Qiu, Qinyin; Yarossi, Mathew; Patel, Jigna; Mont, Ashley J.; Saleh, Soha; Nolan, Karen J.; Barrett, AM; Tunik, Eugene; Adamovich, Sergei V. (Frontiers in Neurology, 2020)
Introduction. Innovative therapies have attempted to reduce arm impairment after stroke, but have not made substantial improvement as over 50% of people post-stroke continue to have sensorimotor deficits affecting their participation in daily activities. Intervention studies have focused on the role of increased dosing, however recent studies have indicated that timing of rehabilitation interventions may be as important as dosing and importantly, that both interact in mediating effectiveness. This study is designed to empirically test this controversy. Methods and analysis. In this single-blinded, interventional study, subjects will be stratified on two dimensions, impairment level (Fugl-Meyer Upper Extremity Assessment (FM) and presence of Motor Evoked Potentials (MEPs) as follows: 1) Severe, FM score 10-19, MEP+, 2) Severe, FM score 10-19, MEP-, 3) Moderate, FM score 20-49, MEP+, 4) Moderate, FM score 20-49, MEP-. Subjects not eligible for TMS will be assigned to group 2 (if severe) or group 3 (if moderate). Stratified block randomization will then be used to achieve a balanced assignment. Early Robotic/VR Therapy group (EVR) will receive inpatient usual care plus 10 hours of intensive therapy focusing on the hand using robotically facilitated rehabilitation interventions presented in virtual environments, initiated 5-30 days post-stroke. Delayed Robotic/VR Therapy group (DVR) will receive the same intervention but initiated 30-60 days post-stroke. Dose-matched usual care group (DMUC) will receive an extra 10 hours of usual care. Usual Care Group (UC) will receive their prescribed physical/occupational therapy. Outcomes: There are clinical, neurophysiological, and kinematic/kinetic measures, plus measures of daily arm use and quality of life. Primary outcome is the Action Research Arm Test (ARAT). Discussion. Outcome measures will be assessed to determine whether there is an optimal early time period in which rehabilitation is most effective, and whether there is a difference in the recapture of premorbid patterns of movement versus the development of an efficient, but compensatory movement strategy. Ethical Considerations. The IRBs of New Jersey Institute of Technology, Rutgers University, Northeastern University, and Kessler Foundation reviewed and approved all study protocols. Study was registered in https://clinical trials.gov (NCT03569059) prior to recruitment. Dissemination will include submission to peer-reviewed journals and professional presentations.